A brief introduction to the search for extra-terrestrial life - Barbieri, Cesare, 1942- (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
This book provides an introduction, from the astronomical point of view of the author,to the exciting search for extra-terrestrial life, and an overview of the current status of research into 'alien' life in the Solar System and beyond. It also explores the potential future human exploration of the Moon and Mars. Up-to-date with the latest developments in the field and accompanied by key references for further study, it is a fantastic introduction to the field of astrobiology for non-science majors taking an elective module, in addition to undergraduates studying physics with an interest in this area. Features: Contains the latest groundbreaking research in the hunt for life outside of Earth Discusses the identification of biosignatures in exo-planets Reviews future options for human outposts on the Moon and Mars
Cosmological process leading to life on Earth -- Events in the Milky Way and Solar system -- Main characteristics of living organisms -- Water and life -- Human outposts on the Moon and on Mars -- Comets, asteroids, meteorites, death and life -- The cometary mission Rosetta -- Planets of nearby stars -- Search for extra-terrestrial intelligence, SETI.
OCLC-licensed vendor bibliographic record.
Keywords: Life on other planets; Extraterrestrial beings; SCIENCE / Physics; SCIENCE / Astrophysics & Space Science